Determinants of Job Performance - Winari, Erni; Isa Indrawan, Muhammad (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Human resource management (HRM) is a field of study and practice that focuses on the management and management of human resources in an organization. The aim is to ensure that the organization has a qualified, motivated and productive workforce to achieve its strategic goals. It is important for organizations to pay attention to human resources because the performance and success of the organization is very dependent on the quality and productivity of the workforce. Investments in HR development can increase employee loyalty, increase retention, reduce recruitment and retraining costs, and increase efficiency and productivity throughout the organization. The results of this research are as follows: Job satisfaction is unable to moderate organizational commitment to job performance with an original sample value of 0.004 and ap value of 0.486. Job Satisfaction is able to moderate and weaken Job Quality on Job Performance with an original sample value of -0.173 and ap value of 0.018. Job Satisfaction has a positive and significant effect on Job Performance with an original sample value of 0.495 and ap value of 0.001. Organizational Commitment has a positive and insignificant effect on Job Performance with an original sample value of 0.098 and ap value of 0.260. Work Quality has a positive and significant effect on Work Performance with an original sample value of 0.203 and ap value of 0.033.